How private are Europe's private forests? A comparative property rights analysis. (July 2018) - Nichiforel, Liviu; Keary, Kevin; Deuffic, Philippe; Weiss, Gerhard; Thorsen, Bo Jellesmark; Winkel, Georg; Avdibegović, Mersudin; Dobšinská, Zuzana; Feliciano, Diana; Gatto, Paola; Gorriz Mifsud, Elena; Hoogstra-Klein, Marjanke; et al.
Highlights: The index of property rights expresses the scope of decision making of private forest owners across five rights domains. Significant variations across Europe in the private forest owners' freedom of decision making is documented. The possibility to set management goals and implement management actions differs considerable. The share of private ownership and the former socio-political background contributes to such variations. The comparative analysis of property rights is essential for the integration of European forest and environmental policies. Abstract: Private forests are widespread in Europe providing a range of ecosystem services of significant value to society, and there are calls for novel policies to enhance their provision and to face the challenges of environmental changes. Such policies need to acknowledge the importance of private forests, and importantly they need to be based on a deep understanding of how property rights held by private forest owners vary across Europe. We collected and analysed data on the content of property rights based on formal legal requirements existing in 31 European jurisdictions. To allow a comparison across jurisdictions, we constructed an original Property Rights Index for Forestry encompassing five rights domains (access, withdrawal, management, exclusion and alienation). We documented substantial variation of the private forest owners' rights, and notably to i) make decisions in operational management and the formulation of management goals, ii) withdraw timber resources from their forest, and iii) exclude others from the use of forest resources. We identified broad relations between the scope for decision making of private forest owners and jurisdictions' former socio-political background and geographical distribution. The variation in the content of property rights has implications for the implementation of international environmental policies, and stresses the need for tailored policy instruments, when addressing European society's rural development, the bioeconomy, climate change mitigation measures and nature protection strategies.